Alelopathic effects of extracts of Tradescantia zebrina in germination of Lactuca sativa - Moura, Danielle Roballo de; Araujo, Emmanoella Costa Guaraná; Silva, Thiago Cardoso; Leão, Shyrlaine Lilian Moura; Lima, Tarcísio Viana de (Revista Ecologia e Nutrição Florestal - ENFLO, 2018)
By releasing allelopathic substances, produced in the secondary metabolism, an individual can influence the development of other organisms in their surroundings. This study aimed to evaluate the effect of aqueous extracts of Tradescantia zebrina Heynh. ex Bosse. (zebrina) in the germination and initial development of seeds of Lactuca sativa L. (lettuce). The experiment was conducted under natural environment conditions (25°C and 72% RH), with extracts leaf and roots of zebrine at concentrations of 100%, 75%, 50% and 25%, using distilled water as a control treatment. Fifty seeds of lettuce were used, uniformly distributed in germitest® paper, duly sterilized and moistened with the solution, in gerbox® boxes, with five replicates. The observations lasted seven days, evaluating the percentage of germination (%G), germination speed index (GSI), mean germination time (t) and average germination velocity (v). These data were submitted to the statistical analysis, after which the applications of leaf extracts and zebrine roots reduced the percentage of germination and the germination speed of lettuce seeds, indicating their allelopathic effect.